Observation and characterization of near-interface oxide traps with C-V techniques - Paulsen, Ron (IEEE Transactions on Electron Devices, 1995)
The anomalous hump observed in low frequency C-V curves of stressed devices is attributed to near-interface oxide traps, rather than so-called "interface" traps. A low frequency C-V model has been developed to interpret the effect of near-interface oxide traps which communicate with the Si-SiO/sub 2/ interface traps and influence C-V characteristics. At low measurement frequencies, electrons have sufficient time to tunnel from interface traps and fill near-interface oxide traps via a trap-to-trap tunneling mechanism. By varying the measurement frequency, a spatial distribution of near-interface oxide traps is obtained. A consistent near-interface oxide trap distribution has been extracted for a trap-rich SONGS memory transistor using both variable frequency Hi-Lo C-V and charge pumping techniques.